Longitudinal relationship between muscle mass and intramuscular adipose tissue of the quadriceps in older inpatients at different activities of daily living levels. (February 2023) - Akazawa, Naoki; Kishi, Masaki; Hino, Toshikazu; Tsuji, Ryota; Tamura, Kimiyuki; Hioka, Akemi; Moriyama, Hideki
Summary: Background & aims: Whether there is a longitudinal relationship between muscle mass and intramuscular adipose tissue of the quadriceps at different activities of daily living (ADL) levels remains unclear. This study aimed to examine the longitudinal relationship between muscle mass and intramuscular adipose tissue of the quadriceps in older inpatients at different ADL levels. Methods: This prospective cohort study was hospital-based and included 198 inpatients aged ≥65 years. Ultrasound images were acquired using B-mode ultrasound imaging. Muscle mass and intramuscular adipose tissue of the quadriceps were assessed based on muscle thickness and echo intensity, respectively. The changes in quadriceps thickness and echo intensity were calculated by subtracting these baseline values from these values at discharge. ADL were assessed at admission using the Barthel Index (BI). The participants were divided into the low BI (BI score <60) and high BI (BI score ≥60) groups in accordance with the BI score. Multiple regression analysis was performed to examine whether the change in quadriceps echo intensity was independently and significantly related to change in quadriceps thickness, even after adjusting for confounding factors in the total participants and high and low BI groups. Results: The number of the high and low BI groups were 54 and 144. Change in quadriceps echo intensity was independently and significantly related to changes in quadriceps thickness of the total participants (β = −0.53, p < 0.01) and low BI (β = − 0.51, p < 0.01) and high BI (β = −0.70, p < 0.01) groups. Conclusions: The results of this study indicate that there is a longitudinal negative relationship between muscle mass and intramuscular adipose tissue of the quadriceps in older inpatients regardless of ADL level. Intramuscular adipose tissue may be an important contributing factor for muscle mass. Highlights: We examined the longitudinal relationship between muscle mass and intramuscular adipose tissue in older inpatients at different ADL levels. Change in quadriceps echo intensity was negatively related to change in quadriceps thickness of the low and high Barthel Index groups. There is a longitudinal negative relationship between muscle mass and intramuscular adipose tissue in older inpatients regardless of ADL level. Intramuscular adipose tissue may be an important contributing factor for muscle mass.